The Carer's Handbook : essential information and support for all those in a caring role - Matthews, Jane. (Oxford : How To Books, 2006)
Jane Matthews gives valuable and comprehensive advice into the whole range of carer's situations, whether that involves shopping for a housebound neighbour, or giving up work to care full-time for a disabled child or confused parent.
Includes bibliographical references and index.
Keywords: Caregivers -- Handbooks, manuals, etc; Society